Intention to Use Humanoid Robotic as Assistive Rehabilitation Treatment for Children with Autism - Amily Fikry; Hamizah Hassan (Journal of Social Transformation and Regional Development, 2019)
Researchers have found that humanoid robotic can be an assistive rehabilitation treatment for Autism children. This paper aims to discover the awareness and the intention of rehab managers to use it at their rehab centers in Malaysia. Two (2) public rehabilitation centers located in the Northern Region of Peninsular Malaysia were selected and two managers and four assistants in each center were interviewed by employing an in-depth interview (IDI) method. The study found that majority of rehab managers and their assistant lack of awareness but intent to use humanoid robotic as an assistive rehabilitation treatment for Autism children at their centers. The findings of this study can aid responsible parties in planning for the public rehab centers to start using humanoid robotic for autism children as an assistive rehabilitation treatment